PROSES BERPIKIR KRITIS PESERTA DIDIK DALAM MEMECAHKAN MASALAH SISTEM PERSAMAAN LINIER DUA VARIABEL DITINJAU DARI GAYA BELAJAR KELAS IX B SMP NEGERI 2 SURAKARTA TAHUN PELAJARAN 2015/2016 - Marfuah, Ismiyati; Mardiyana, Mardiyana; Subanti, Sri (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract. This research aimed to describe the studentsâ critical thinking process with visual, auditory, and kinesthetic learning style to solve the linear equations system of two variables. The subjects of this qualitative research were students of IXB class of SMPN 2 Surakarta year 2015/2016 that were selected by purposive sampling. The data was collected by interview based task. The data analysis used data reduction, data display, and conclusion drawing. The results showed: (1) visual students: (a) identification: the students interprete and examine the problems exactly. (b) analysis: the students could integrate the informations to formulate the problems to linear equations system of two variables and determine the solving methods exactly. (c) evaluation: the students could apply the methods correctly, investigate the answers, and make conclusion in accordance with problems. (2) auditory students: (a) identification: the students interprete and examine the problems exactly. (b) analysis: there is student that could integrate the informations to formulate the problems and determine the solving methods. There is also student that could not formulate the problems to linear equations system of two variables. (c) evaluation: there is student that could apply the methods correctly, investigate the answers, and make conclusion in accordance with problems. There is also student that could not solve the problems into linear equations system of two variables. (3) kinesthetic students: (a) identification: the students interprete and examine the problems exactly. (b) analysis: there is student that could integrate the informations to formulate the problems and determine the solving methods. There is also student that could not formulate the problems to a system of linear equations of two variables. (c) evaluation: there is student that could apply the methods correctly, investigate the answers, and make conclusion in accordance with problems. There is also student that could not solve the problems into linear equations system of two variables.Keywords: critical thinking process, linear equations system of two variables problem solving, learning stylesÂ